Modern Urdu Fiction and Sufism: An Analytical Study - Awaisi, Muhammad Arshad; Attaullah, Muhammad; Arshad, Waseem (sourcecoder, 2023)
Fiction writers of the 21st century have added to the structure and technique of this modern fiction by driving psychological conditions, complications, pressure of time and circumstances, realism of political and social situation, symbols, metaphors and aesthetics. In Urdu fiction, in the last decade of the 20th century, the writers of fiction, if not directly, but behind-the-scenes, have definitely reflected mystical experiences. These fiction writers include Intizar Hussain, Khalida Hussain, Asad Muhammad Khan, Mumtaz Mufti, Ashfaq Ahmed, Muhammad Saeed Sheikh etc